Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1074/jbc.m610749200
|View full text |Cite
|
Sign up to set email alerts
|

Repression of p53-mediated Transcription by Adenovirus E1B 55-kDa Does Not Require Corepressor mSin3A and Histone Deacetylases

Abstract: The Ad E1B 55-kDa protein (E1B) is a potent transcriptional repressor. In vitro biochemical studies revealed that direct p53-E1B interaction is essential for E1B to block p53-activated transcription and a corepressor may be involved. To understand how E1B represses p53-mediated transcription in vivo, we expressed E1B in several tumor cell lines that express wild type p53. Here we show that E1B strongly suppresses the expression of p53 target genes such as p21 and Puma-␣ in normal growth conditions or after cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
(70 reference statements)
3
11
0
Order By: Relevance
“…However, such mutations neither induced increased expression of E1B 55-kDa protein-repressed genes in infected HFFs (44) nor increased the sensitivity of viral replication (Table 1) or DNA synthesis (data not shown) to IFN. The E1B protein alone is sufficient to repress p53-dependent transcription in cells transiently or stably synthesizing the viral protein (35,37,38,(75)(76)(77)(78). The E1B 55-kDa protein fully competent to rescue the defects in genome replication of the null mutant AdEasyE1⌬2347 when stably produced in HFFs (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, such mutations neither induced increased expression of E1B 55-kDa protein-repressed genes in infected HFFs (44) nor increased the sensitivity of viral replication (Table 1) or DNA synthesis (data not shown) to IFN. The E1B protein alone is sufficient to repress p53-dependent transcription in cells transiently or stably synthesizing the viral protein (35,37,38,(75)(76)(77)(78). The E1B 55-kDa protein fully competent to rescue the defects in genome replication of the null mutant AdEasyE1⌬2347 when stably produced in HFFs (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Substitutions of the C-terminal sites of phosphorylation of the Ad5 or Ad12 E1B protein reduced its ability to inhibit p53-dependent transcription or to act as a repressor when fused to a heterologous DNA-binding domain (37,75,76). However, such mutations neither induced increased expression of E1B 55-kDa protein-repressed genes in infected HFFs (44) nor increased the sensitivity of viral replication (Table 1) or DNA synthesis (data not shown) to IFN.…”
Section: Discussionmentioning
confidence: 99%
“…The E1B-55K protein has also been shown to be a strong repressor of basal transcription (157), but interestingly, this activity requires a cellular corepressor which has not yet been identified (103). The E1B-55K protein interacts with a Sin3A/histone deacetylase 1 corepressor complex, but this is apparently not required for the transcriptional repression activity of the E1B-55K protein (118,160). It is therefore tempting to speculate that the identity of this elusive corepressor is E1B-AP5, and it will be interesting to determine if this is the case.…”
Section: E1b-55k and Cellular Binding Proteinsmentioning
confidence: 99%
“…E1B-55K forms a stable complex with DNAbound p53 and increases p53's binding affinity to its cognate DNA-binding site in vitro (30). Chromatin immunoprecipitation experiments revealed that E1B-55K also associates with the promoters of endogenous p53 target genes such as the p21 gene (57). Association of E1B-55K with p53 represses p53-mediated transcription in vitro and in cells (31,52,57).…”
mentioning
confidence: 99%
“…Chromatin immunoprecipitation experiments revealed that E1B-55K also associates with the promoters of endogenous p53 target genes such as the p21 gene (57). Association of E1B-55K with p53 represses p53-mediated transcription in vitro and in cells (31,52,57). It has been suggested that a cellular corepressor is required for E1B-55K to inhibit p53-activated transcription (31).…”
mentioning
confidence: 99%